The hormonal mechanism of intestinal adaptation - Sagor, Geoffrey Roland (Department of Surgery, 2018)
The gastrointestinal tract has a large functional reserve. This is particularly true of the small intestine, and early studies by Flint in 1912, showed that dogs could withstand 50%-70% small intestinal resection, returning to normal health after an initial period of weight loss and malabsorption. No doubt, this reserve is in part due to the very high rate of epithelial proliferation in small bowel mucosa. Intestinal adaptation is the result of morphological and functional changes, and while these parameters can be accurately appreciated, the mechanisms by which these changes take place, are still under active investigation. This section summarises the changes, both structural and functional, in the adaptive process, and this is followed by a review of the background work done on the possible mechanism of adaptation. The normal anatomy of intestinal mucosa is however, considered first. Most of the work done to date in the field of intestinal adaptation, involves the small bowel, and this part of the gut will be discussed predominantly, but data available on colonic growth will be mentioned.